At the Movies: Avoiding Head-to-Head Competition on the Big Screen: The Economics of Movie Distribution - Darren Filson; Fernando Fabre; Alfredo Nava; Paola Rodriguez (Claremont McKenna College, Department of Economics, 2000)
This paper provides theoretical explanations for devices that movie distributors use to avoid head-to-head competition. We use a simple static model to show how revenuse sharing exhibition contracts providex multiplex owners with incentives to take cross effects on demand into account. Then we simulate a dynamic version of the model to explian the practice of staggering the release dates of hit movies and consider how vertical integration affects release patterns and the allocation of movies to screens. The dynamic model is of independent interest because it allows for dynamic strategic interaction in a common agency framework.
Keywords: L14; L22; L82; 330; common agent; exclusive dealing; entertainment; film; licensing